2010
DOI: 10.1186/1471-2458-10-654
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiovascular risk factors between sri lankans living in kandy and oslo

Abstract: BackgroundSouth Asians living in western countries are known to have unfavourable cardiovascular risk profiles. Studies indicate migrants are worse off when compared to those living in country of origin. The purpose of this study was to compare selected cardiovascular risk factors between migrant Sri Lankans living in Oslo, Norway and Urban dwellers from Kandy, Sri Lanka.MethodsData on non fasting serum lipids, blood pressure, anthropometrics and socio demographics of Sri Lankan Tamils from two almost similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 27 publications
(57 reference statements)
2
34
1
Order By: Relevance
“…Comparative studies with samples of Asian immigrants showed mixed results. While Mahajan & Bermingham 43 and Tennakoon et al 46 reported a better cardiovascular risk profile in immigrants living in Sydney (Australia) and Oslo, respectively, Bhatnagar et al 45 found the opposite in immigrants living in England. The first study had several limitations.…”
Section: Asiansmentioning
confidence: 98%
See 4 more Smart Citations
“…Comparative studies with samples of Asian immigrants showed mixed results. While Mahajan & Bermingham 43 and Tennakoon et al 46 reported a better cardiovascular risk profile in immigrants living in Sydney (Australia) and Oslo, respectively, Bhatnagar et al 45 found the opposite in immigrants living in England. The first study had several limitations.…”
Section: Asiansmentioning
confidence: 98%
“…Two studies 43,45 used relatives as controls. Five of the studies 45,46,47,48,49 reported that immigrants had a higher BMI than the control group. A study of Indian immigrants living in Australia 43 showed no significant difference in BMI among men.…”
Section: Comparison Of Immigrants With Respective Home-country Residentsmentioning
confidence: 99%
See 3 more Smart Citations